STRATEGI PENGEMBANGAN USAHA MELALUI PEMASARAN DIGITAL PADA UMKM ESHAN.ID_ BEJI DEPOK - Silaningsih, Endang; Fitriyani , Elma; Alfahri, Hasanudin; Kartini, Tini (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
UMKM play an important role in the economy in Indonesia. UMKM can play a role in improving people's welfare as a means of equalizing the economic level of the common people, a means of alleviating poverty and a means of earning foreign exchange for the country. Despite the importance of the contribution of UMKM to the national economy, it turns out that this sector still has many problems, one of which is the weakness of UMKM in marketing their products. The purpose of community service is to provide assistance to UMKM related to the use of digital technology to increase product sales, especially to UMKM Eshan.id_. Ehsan.id_ UMKM is a business in the field of knitting handicrafts, which in 2022 has achieved an income target of only 63.05%, so it is necessary to determine the right strategy in marketing its products, such as through digital marketing. The assistance is intended so that UMKM can take advantage of social media to increase sales by creating social media content on Instagram and Tiktok. The result of this activity is the giving of meaning and philosophy to the logo to meet the requirements for making IPR (Intellectual Property Rights) and also a company profile that can be used by UMKM in conducting product marketing. In addition, UMKM owners also receive education regarding the theory of digital product marketing through social media that is effective and right on target